Algorithm of NAF scalar multiplication on ECC against SPA - Min WANG; Zhen WU (Tongxin xuebao)
Against the problem that non-adjacent form(NAF)scalar multiplication on Elliptic curve cryptography(ECC) were not well resist the simple power attack(SPA),the implementation of NAF scalar multiplication and the mechanism of SPA attack were analyzed.Then a new algorithm,named equal power NAF scalar multiplication was presented.It was verified that equal power NAF scalar multiplication was efficient countermeasure against SPA attack by experimental analysis on power traces of the smartcard collected from the power analysis platform.